(untitled) (African Journal of Law and Politics, 2023)
The presumption of innocence is a guiding principle of modern criminal procedure laid down in numerous international and national texts aimed at guaranteeing the effectiveness of a fair trial and the protection of the individual rights and freedoms of any person prosecuted in a criminal trial. This principle, which was established in response to the inquisitorial procedures of totalitarian systems that used presumptions of guilt, and which has been enshrined in Cameroonian law, is today being abused and very little respected in the judicial practice of repressing terrorism and the instruments of an increasingly preventive State. This lack of respect, which is rarely sanctioned, is worrying in view of the damage done to the credibility of Cameroonian justice and calls for greater audacity and independence on the part of magistrates responsible for dealing with terrorism cases.